Systemic Ketone Replacement Does Not Improve Survival or Cancer Cachexia in Mice With Lung Cancer - Langer, Henning Tim; Ramsamooj, Shakti; Liang, Roger J.; Grover, Rahul; Hwang, Seo-Kyoung; Goncalves, Marcus DaSilva (Frontiers in Oncology, 2022)
Cachexia is a debilitating comorbidity affecting many lung cancer patients. We have previously found that cachectic mice with lung cancer have reduced serum ketone body levels due to low PPARα activity in the liver. Restoring hepatic PPARα activity with fenofibrate increased circulating ketones and delayed muscle and white adipose tissue wasting. We hypothesized that the loss of circulating ketones plays a pathophysiologic role in cachexia and performed two dietary intervention studies to test this hypothesis. In the first study, male and female mice were randomized to consume either a very low carbohydrate, ketogenic diet (KD) or normal chow (NC) after undergoing tumor induction. The KD successfully restored serum ketone levels and decreased blood glucose in cachectic mice but did not improve body weight maintenance or survival. In fact, there was a trend for the KD to worsen survival in male but not in female mice. In the second study, we compounded a ketone ester supplement into the NC diet (KE) and randomized tumor-bearing mice to KE or NC after tumor induction. We confirmed that KE was able to acutely and chronically increase ketone body abundance in the serum compared to NC. However, the restoration of ketones in the circulation was not able to improve body weight maintenance or survival in male or female mice with lung cancer. Finally, we investigated PPARα activity in the liver of mice fed KE and NC and found that animals fed a ketone ester supplement showed a significant increase in mRNA expression of several PPARα targets. These data negate our initial hypothesis and suggest that restoring ketone body availability in the circulation of mice with lung cancer does not alter cachexia development or improve survival, despite increasing hepatic PPARα activity.